Ectopia cordis - Arzu, Jahanara; Siddique, Md Abu; Banerjee, Sajal K; Ahmed, Chowdhury Meshkat; Haque, Md Harisul; Sheikh, Naveen; Mahmood, Manzoor (University Heart Journal, 2015)
Ectopia cordisis characterized by partial or complete displacement of the heart out of the thoracic cavity The defect is a rare congenital abnormality, occurring in 5.5 to 7.9 per 1 million live births. University Heart Journal Vol. 9, No. 2, July 2013; 119-120